2022
DOI: 10.1002/pros.24313
|View full text |Cite
|
Sign up to set email alerts
|

Non‐organ confined stage and upgrading rates in exclusive PSA high‐risk prostate cancer patients

Abstract: Background: The pathological stage of prostate cancer with high-risk prostatespecific antigen (PSA) levels, but otherwise favorable and/or intermediate risk characteristics (clinical T-stage, Gleason Grade group at biopsy [B-GGG]) is unknown. We hypothesized that a considerable proportion of such patients will exhibit clinically meaningful GGG upgrading or non-organ confined (NOC) stage at radical prostatectomy (RP). Materials and methods: Within the Surveillance, Epidemiology, and End Results database (2010-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In prostate cancer, the discrepancy between the biopsy Gleason score and the radical prostatectomy (RP) Gleason score is a well-known phenomenon [1][2][3][4][5][6][7][8]. In particular, upgrading has been thoroughly studied in several single-and multi-institutional, as well as population-based databases [8][9][10][11][12]. Conversely, data that can be used to examine downgrading rates, particularly in biopsied high-risk prostate cancer patients, are limited due to the rarity of patients with Gleason scores ≥4 + 4 undergoing RP [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In prostate cancer, the discrepancy between the biopsy Gleason score and the radical prostatectomy (RP) Gleason score is a well-known phenomenon [1][2][3][4][5][6][7][8]. In particular, upgrading has been thoroughly studied in several single-and multi-institutional, as well as population-based databases [8][9][10][11][12]. Conversely, data that can be used to examine downgrading rates, particularly in biopsied high-risk prostate cancer patients, are limited due to the rarity of patients with Gleason scores ≥4 + 4 undergoing RP [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, cT1–2 patients exhibited PSA > 20 ng/ml in 22% and biopsy GGG IV–V in 86% of cases. To further support the importance of other high‐risk features beyond clinical stage, Hoeh et al 23 reported an unexpected high rate of non‐organ confined disease (51%) in exclusive PSA high‐risk PCa patients. Consequently, lower rate of SVI in cT3a compared to cT2 patients might be due to the fact that these patients harbored less aggressive features (PSA and GGG) than cT2 counterparts when NCCN high‐risk only PCa patients are considered.…”
Section: Discussionmentioning
confidence: 99%
“…In Partin’s table, risk of recurrence is highest at PSA 6.1–10 and >10 [ 14 ]. This conflict testifies to the lack of uniformity in gauging the predictive ability of PSA vis-à-vis survivorship of PCa [ 22 ]. Toward resolving this ambivalence, there is a need to examine the relationship between PSA and survivorship of PCa.…”
Section: Introductionmentioning
confidence: 99%